Análise comparativa de diferentes tratamentos para reduzir a deterioração de tomates - Rosanova, Aline de Holanda (2013)
Due to their high moisture content, tomatoes have a high metabolic activity that continues even after harvesting, making them a highly perishable vegetable. According to FAO, Brazil is the largest tomato producer in South America and the eighth largest producer in the world. Despite this significant production, rapid fruit deterioration causes a loss of about 40% of this production in post-harvesting operations such as transportation and storage. Recently, new techniques have been tested to increase the shelf life of vegetables, such as the use of high voltage electric fields to produce a modified atmosphere in which the ionization induced by corona discharge contributes to retarding deterioration by mechanisms such as the decreasing respiratory rates, destroying ethylene and producting ozone. Therefore, the objectives of this study were to set up, check and test equipment to carry out experiments to treat different types of fruit and vegetables using electric fields. In this work this system was used for tomatoes and its effectiveness was evaluated by analyzing some measurable quality properties such as loss of mass, changes in skin color, fruit firmness, total titratable acidity (ATT) and soluble solids content (SST). This method was compared to the use of refrigeration to extend the shelf life of this vegetable. An improvement of some measurable quality properties was observed after treating tomatoes cv. Andrea Victory intermittently by applying an electrical field of -1.6 kV/cm followed by storage in climate chamber or using -2.0 kV/cm followed by storage at room temperature, and also after using continuous treatments in tomatoes cv. Paron (-1.9 kV/cm) followed by storage at room temperature. The other measured properties did not indicate benefits of electrical field treatment for preserving the fruit quality. Storage of tomatoes cv. Paron at 15.0 oC and relative humidity of 70% reduced the loss of mass and improved fruit firmness in comparison to the control group, while the storage in a domestic refrigerator reduced the loss of mass and improved the skin color of the vegetables. Concerning the treatment techniques electric fields and refrigeration, a clear advantage of one compared to the other was not identified, since both had a positive effect on at least one property investigated.